2013
DOI: 10.1038/srep03087
|View full text |Cite
|
Sign up to set email alerts
|

Multi-photon absorption limits to heralded single photon sources

Abstract: Single photons are of paramount importance to future quantum technologies, including quantum communication and computation. Nonlinear photonic devices using parametric processes offer a straightforward route to generating photons, however additional nonlinear processes may come into play and interfere with these sources. Here we analyse spontaneous four-wave mixing (SFWM) sources in the presence of multi-photon processes. We conduct experiments in silicon and gallium indium phosphide photonic crystal waveguide… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 58 publications
4
49
0
Order By: Relevance
“…As silicon's energy bandgap is approximately twice as much as the energy of one photon at around 1,550 nm, it can absorb two photons when the incident light has a high intensity and introduce two-photon absorption (TPA) losses. As shown in [62], in single-photon generation experiments, TPA does not only occur between two pump photons but also happens between one pump photon and one generated photon, introducing extra losses to the generated photons. Furthermore, once silicon devices absorb some photons, some electrons will become free carries and these free carries can absorb additional photons, introducing free-carrier absorption (FCA) losses to both pump and generated photons.…”
Section: Nonlinear Losses Of Siliconmentioning
confidence: 99%
See 1 more Smart Citation
“…As silicon's energy bandgap is approximately twice as much as the energy of one photon at around 1,550 nm, it can absorb two photons when the incident light has a high intensity and introduce two-photon absorption (TPA) losses. As shown in [62], in single-photon generation experiments, TPA does not only occur between two pump photons but also happens between one pump photon and one generated photon, introducing extra losses to the generated photons. Furthermore, once silicon devices absorb some photons, some electrons will become free carries and these free carries can absorb additional photons, introducing free-carrier absorption (FCA) losses to both pump and generated photons.…”
Section: Nonlinear Losses Of Siliconmentioning
confidence: 99%
“…[31] has shown that using electrodes to apply a voltage bias to a silicon device can remove free carries and thus significantly improve the source quality, it is more difficult to reduce TPA. It is possible to use a different material such as GaInP that has a large bandgap to prevent TPA; however, it won't replace silicon unless the fabrication becomes more mature to bring the linear losses down [62].…”
Section: Nonlinear Losses Of Siliconmentioning
confidence: 99%
“…Finally, in Fig. 4(g), we show the coincidence-toaccidental ratio [19,80,82] as a function of the pump power in chip A. A value of 50 AE 6-far above the classical limit of 2 and allowing for high-fidelity preparation of entangled-photon pairs or heralded single photons-is achieved under 0.3-mW pump power.…”
Section: Chip-to-chip Transfer Demultiplexing and Correlation Mementioning
confidence: 99%
“…Here we discuss the use of resonant structures, such as micro-rings [93,97], photonic crystal waveguides [98,101,102], CROWs [41,99] and micro-disks [100] to enhance SFWM.…”
Section: Sfwm In Resonant Structuresmentioning
confidence: 99%